Atqasuk LAI Measurements (ASCII). Version 1.0 ... - Walker, D.; Moody, A. (UCAR/NCAR - Earth Observing Laboratory, 2011)
This dataset contains leaf area index (LAI) measurements taken at peak biomass at the Atqasuk site on the Arctic Slope of Alaska, for the Arctic Transitions in the Land-Atmosphere System (ATLAS) project. The data were collected in 1999 and are in ASCII format. See the README for additional information. ...